(untitled) (Scientific journal of the Fergana State University, 2023)
A vermiculite was treated with acid. The new adsorbent, a polyacrylonitrile / vermiculite composition, was synthesized. Adsorption of the obtained sorbent in aqueous solutions of chromium (VI), copper (II) and nickel (II) was studied.